Effects of Cooperative Learning Models and Gender on Basketball Skills (Universitas Pendidikan Indonesia, 2024)
This research aimed to analyze the effect of two types of cooperative learning models, namely Student Teams-Achievement Division (STAD) and Team Games Tournament (TGT), and gender on basketball skills. This research used a 2x2 factorial design and involved 36 students divided by gender and learning model. Basic basketball skill tests included passing, dribbling, and shooting tests. The treatment was conducted for 8 weeks. The pre-test and post-test were administered to measure changes in basketball skills. Data were analyzed using two-way Analysis of Variance (Two-Way ANOVA) to examine the effect of the learning models, gender, and their interaction on basketball skills. The results showed that the TGT learning model was more effective in improving the student basketball skills compared to the STAD model. In addition, there was a significant difference in basketball skills between male and female students, with male students showing better results. However, there was no significant interaction between the learning models and gender with the student basketball skills.